A low profile miniaturized widely‐spaced triband bandpass FSS using coupled resonance. Issue 11 (23rd August 2020) - Wu, Chen; Liu, Shaobin; Yu, Qiming; Kong, Xiangkun; Yuan, Jing; Liao, Kun
Abstract: In this article, a triband highly selective widely‐spaced bandpass frequency‐selective surface (FSS) is presented. The proposed FSS is consisted of five metal layers that are separated from each other by four dielectric substrates. Using coupled resonance between layers, three passbands operating at 11.0, 17.4, and 31.9 GHz are achieved. Meanwhile, the dimension of the unit cell of the FSS can be achieved in 0.139 λ 0 × 0.139 λ 0 ( λ 0 is the wavelength of the first resonant frequency in the free‐space), and the overall thickness can be 0.057 λ 0, exhibiting miniaturization and low profile characteristics. Due to the proposed FSS can provide multitransmission zeros between two adjacent passbands, the relative bandwidth of the spacing between the second passband and the third passband can reach 58.8% from 17.4 to 31.9 GHz. Thus, a widely spaced response is achieved. In practical, the proposed FSS has an important role in the radio cross‐sectional reduction of some military systems, such as homing head, which can simultaneously detecting mid‐range and long‐range targets. Furthermore, the FSS shows the stable response of angles for both TE and TM polarizations. The equivalent circuit model (ECM) is provided to analysis its operating principle. Finally, a prototype of the proposed FSS is simulated, fabricated and measured. The measured results are in good agreement with the simulation ones.